Intelligent Attention Rehabilitation System (2021)
The present invention provides an intelligent attention rehabilitation system, which includes a gaze tracking module, an attention evaluation module, an intelligent computation and program push module, a data storage module, and an assessment and feedback module. In the invention, based on the theoretical CMA, data on attention level is acquired; and the advantages of simple configuration requirements and low cost of the gaze tracking technology, and intelligent computation of AI algorithms are used, to digitally evaluate attention of a subject. Besides, the DQN algorithm is used to realize intelligent push of related attention training guidance and programs, to solve the problem of family attention rehabilitation training under the lack of scientific guidance in the market currently, thereby providing a more scientific and accurate family attention rehabilitation evaluation and training system for the need.